1977
DOI: 10.1098/rspa.1977.0141
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the strain rate in the zone of intense shear in which the chip is formed in machining from the dynamic flow stress properties of the work material and the cutting conditions

Abstract: In previous applications of an approximate machining theory in which account is taken of the strain rate and temperature dependence of the work material flow stress properties it has been found necessary to use an empirical relation to determine the maximum value of the maximum shear strain rate in the chip formation zone. In this paper the machining theory is further developed so that this strain rate can be obtained as part of the solution. Predicted values found in this way are shown to be in excellent agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…After that, many slip-line models have been proposed. In 1977, the parallel-sided shear zone theory proposed by Oxley et al [16] is an important progress in modeling cutting process, as shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…After that, many slip-line models have been proposed. In 1977, the parallel-sided shear zone theory proposed by Oxley et al [16] is an important progress in modeling cutting process, as shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…A high rake angle generates a shear angle increasing and so a reduction of cutting force. This phenomenon can be illustrated by the Oxley and Hasting (1977) model. To conclude, the rake angle choice must be a compromise between a cutting force reduction and a better tool mechanical aspect.…”
Section: Rake Anglementioning
confidence: 99%
“…The rake angle increasing reduces the effective shear angle and friction force. Oxley and Hasting (1977) demonstrate in their model that the cutting temperature is function of shear flow stress, friction force, chip velocity and shear velocity. In fact, whatever the cutting speed, a cutting forces decreasing reduce the cutting temperature.…”
Section: Rake Anglementioning
confidence: 99%
“…For the width of the primary shear zone, the study of Oxley and Hastings [33] shows that the ratio of it and the length of shear plane is 5.9 for carbon steel; thus, there is,…”
Section: Fig 6 Change Of Deformation Coefficient With Cutting Speedmentioning
confidence: 99%